Morphologies and elemental compositions of calcium crystals in phyllodes and branchlets of Acacia robeorum (Leguminosae: Mimosoideae) - He, Honghua (Oxford University Press, 2012)
BACKGROUND AND AIMS: Formation of calcium oxalate crystals is common in the plant kingdom, but biogenic formation of calcium sulfate crystals in plants is rare. We investigated the morphologies and elemental compositions of crystals found in phyllodes and branchlets of Acacia robeorum, a desert shrub of north-western Australia. METHODS: Morphologies of crystals in phyllodes and branchlets of A. robeorum were studied using scanning electron microscopy (SEM), and elemental compositions of the crystals were identified by energy-dispersive X-ray spectroscopy. Distributional patterns of the crystals were studied using optical microscopy together with SEM. KEY RESULTS: According to the elemental compositions, the crystals were classified into three groups: (1) calcium oxalate; (2) calcium sulfate, which is a possible mixture of calcium sulfate and calcium oxalate with calcium sulfate being the major component; and (3) calcium sulfate · magnesium oxalate, presumably mixtures of calcium sulfate, calcium oxalate, magnesium oxalate and silica. The crystals were of various morphologies, including prisms, raphides, styloids, druses, crystal sand, spheres and clusters. Both calcium oxalate and calcium sulfate crystals were observed in almost all tissues, including mesophyll, parenchyma, sclerenchyma (fibre cells), pith, pith ray and cortex; calcium sulfate · magnesium oxalate crystals were only found in mesophyll and parenchyma cells in phyllodes. CONCLUSIONS: The formation of most crystals was biologically induced, as confirmed by studying the crystals formed in the phyllodes from seedlings grown in a glasshouse. The crystals may have functions in removing excess calcium, magnesium and sulfur, protecting the plants against herbivory, and detoxifying aluminium and heavy metals.